BS ISO 13741-1. Plastics/rubber. Polymer dispersions and rubber latices (natural and synthetic). Determination of residual monomers and other organic components by capillary-column gas chromatography. Part 1. Direct liquid injection method (2nd February 2021) - British Standards Institution
No abstract available